MODEL PENGEMBANGAN POTENSI AGROWISATA DI PT CENGKEH ZANZIBAR (PLANTERA) PATEAN KENDAL - Nina Mistriani; RudiPrasetyoArid (Jurnal Pengabdian Masyarakat Waradin, 2022)
This community service activity at Plantera Patean Kendal Agro-tourism is carried out in order to fulfill the request of Plantera Patean Kendal Agro-tourism (PT Cengkeh Zanzibar). As well as the implementation of community service by several lecturers who have knowledge and skills about tourism. This activity was in the form of an analysis FGD on the packaging of agro-based tourism products based on market segmentation. The main objective of this activity is to assist Plantera Agro-tourism in developing agro-tourism potential. As well as providing benefits in the form of training and skills related to the tourism sector.